FAMILY SUPPORT AND EMOTIONAL DISTRESS ON SELF-CARE BEHAVIOR IN PATIENTS WITH DIABETES MELLITUS AT PUSKESMAS GAMPING 1 SLEMAN - Mahardika Primadani; Esti Kurniasih; Sitti Nur Djannah; Nurul Kodriati; Surahma Asti Mulasari (Indonesian Journal for Health Sciences, 2023)
Diabetes mellitus (DM) is a chronic disease caused by genetic factors and an unhealthy lifestyle. The emotional state of a person diagnosed with DM is also very influential on treatment and self-care. To prevent chronic complications, it is necessary to control DM, one of which is self-care for DM patients. The purpose of this study was to determine the relationship between family support and emotional distress on self-care behavior in DM sufferers at the Gamping 1 Health Center in Sleman. The design used in this study is analytic observational with a cross sectional approach. Samples were taken by random sampling of 30 DM patients who participated in PROLANIS activities at the Gamping 1 Health Center in Sleman. Data analysis used the Spearman test. The results showed that there was a significant relationship between family support and emotional distress on self-care behavior in DM patients with a p value of 0.023 0.05 and a correlation coefficient (R = 0.413). This means that the higher the family support, the higher DM sufferers are in carrying out self-care behavior. Likewise with the emotional distress variable with a p value of 0.028 0.05 and a correlation coefficient (R = -0.191). This means that the higher the emotional distress of DM sufferers, the lower DM sufferers are in carrying out self-care behavior